Degradation kinetics and characterization of degradation products of losartan potassium by LC-MS/MS method - Dobričić Vladimir; Marković Bojan (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2019)
This paper presents study of losartan potassium stability evaluation by liquid chromatography with UV/VIS and MS-MS detection and its degradation profile. A solution of losartan potassium was exposed to the following stress agents: 0.1 M HCl, 0.1 M NaOH, and 3% (v/v) H2O2. The analyses of losartan potassium solutions were carried out in a gradient elution mode with acetonitrile and 0.1% (v/v) CF3COOH aqueous solution and constant flow rate of 0.5 mL min-1 within 22 min run time. After 7 days of losartan potassium solutions exposure to the stress agents at room temperature, it was found that the degree of degradation in the presence of 0.1 M HCl and 0.1 M NaOH was less than 1%, while in the presence of 3% H2O2 degradation was significantly higher (about 10%). Chemical structure elucidation of the major degradation products of losartan potassium was performed using LC-MS/MS method. The concentration versus time plot indicated that in 3% (v/v) H2O2 solution losartan potassium was degraded according to the pseudo zero-order reaction kinetics with 1.48·10-8 mol L-1 day-1 rate constant.